Những nhân tố ảnh hưởng đến chất lượng quan hệ giữa người tiêu dùng với công ty: Kết quả kiểm định PLS-SEM và mạng nơ-ron nhân tạo - Nguyễn Nhan Như , Ngọc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The study examines the key factors affecting the relationship quality between consumers and company. The highlights of the study are (1) integrating corporate social responsibility, customer value, and price fairness into the research model that explains the relationship quality variance from a consumer perspective, (2) proposing ethical value as a type of customer value in the context of corporate social responsibility-related consumption, (3) using the multi-analytical approach to accurately assess the complex relationships between the variables in the research model. The results of PLS-SEM analysis show that the hypothetical model is in goodness of fit to the data, and find out the most important role of customer value to relationship quality, followed by corporate social responsibility and then price fairness. The artificial neural network results credently confirm the PLS-SEM results.